Impact of Soybean Phytoestrogen-Rich Extract on Markers of Inflammation Markers in 4-Vinyl Cyclohexane Diepoxide-Induced Menopause in Albino Rats - Edusola Juliana Olaniyan; Mathias Abiodun Emokpae; Fidelis Ohiremen Oyakhire; Ahmed Liasu Adeagbo; Iria Kelly Esezobor; Stephen Olawale Olaniyan (Medical Laboratory Technology Journal, 2023)
The vasomotor symptoms of menopause, including hot flashes, sweating, physical and psychological discomfort, and emotional changes, are accurate and experienced by many of the menopausal and postmenopausal female population. In addition, it causes osteoporosis and slowed metabolism, raising the chance of developing many different ailments. Given that hormone replacement therapy (HRT) has been linked to an increased cancer risk, this investigation was undertaken to identify viable alternatives. The study aimed to investigate the impact of Soybean phytoestrogen-rich extract on some markers of inflammation of 4-vinyl cyclohexene diepoxide-induced menopause in albino rats. Sixty-five (65) female albino Wistar rats were employed in the investigation. Each one was induced with 80mg/kg of 4-vinyl cyclohexene diepoxide before being treated with either normal estradiol therapy (14ug/kg) or varying concentrations of the soybean phytoestrogen-rich extract (200 mg/kg, 400 mg/kg, and 600 mg/kg). Inflammatory markers (C-reactive protein (CRP), interleukin-6 (IL-6), and tumour necrosis factor-alpha (TNF-α)) were measured by ELISA methods. Statistical software SPSS (IBM) version 23.0 was used to analyze the data. Compared to the positive control group, the soybean phytoestrogen-rich extract therapy group saw a dose-dependent reduction in CRP and IL-6 levels (p<0.05) but not in TNF-α (P>0.05). Data from this research demonstrate the anti-inflammatory effects of soybean phytoestrogen-rich extract therapy in menopause-induced female Wistar rats. Soybean phytoestrogen-rich extract therapy in a high dose appears to show no significant difference from hormone replacement therapy as an alternate estrogen source in managing inflammation as a chronic disease.